Randomised clinical trial: tegoprazan, a novel potassium‐competitive acid blocker, or lansoprazole in the treatment of gastric ulcer - Cho, Yu Kyung; Choi, Myung‐Gyu; Choi, Suck Chei; Lee, Kee Myung; Kim, Tae Oh; Park, Soo‐Heon; Moon, Jeong Seop; Lim, Yun Jeong; Kang, Dae Hwan; Cheon, Gab Jin; Baik, Gwang Ho; Kim, Kyoung Oh; et al. (Alimentary pharmacology & therapeutics, 2020)
Summary Background Tegoprazan is a novel potassium‐competitive acid blocker for the treatment of acid‐related disorders. Aims To assess whether tegoprazan is non‐inferior to lansoprazole in terms of efficacy and safety in patients with gastric ulcers. Methods In this phase 3, double‐blind, active control, multicentre study, 306 gastric ulcer patients were randomised to one of three treatment groups: tegoprazan 50 mg, tegoprazan 100 mg and lansoprazole 30 mg once daily for 4 or 8 weeks. The primary endpoint was the cumulative proportion of patients with healed ulcers confirmed by endoscopy up to 8 weeks from treatment initiation. Symptoms and safety were assessed. Results In the full analysis set, the cumulative healing rates at week 8 were 94.8% (91/96) for the tegoprazan 50 mg, 95.0% (94/99) for the tegoprazan 100 mg and 95.7% (89/93) for the lansoprazole 30 mg groups. At week 4, the respective healing rates were 90.6% (87/96), 91.9% (91/99), and 89.2% (83/93). In per protocol analysis, 4‐week healing rates were 95.4% (84/88), 94.6% (88/93) and 92.9% (79/85) for tegoprazan 50 mg, tegoprazan 100 mg and lansoprazole 30 mg, respectively. Both doses of tegoprazan were non‐inferior to lansoprazole in ulcer healing at 4 and 8 weeks. The incidence of drug‐related treatment‐emergent adverse events did not differ among groups. The increase in serum gastrin concentration was not higher in tegoprazan‐treated patients than in lansoprazole‐treated patients. Conclusions Tegoprazan 50 or 100 mg were not inferior to lansoprazole 30 mg once daily in the treatment of gastric ulcers.